In situ studies of oxide nucleation, growth, and transformation using slow electrons. Issue 2 (May 2018) - Flege, Jan Ingo; Grinter, David C.
Abstract: Surface processes such as metal oxidation and metal oxide growth invariably influence the physical and chemical properties of materials and determine their interaction with their surroundings and hence their functionality in many technical applications. On a fundamental level, these processes are found to be governed by a complex interplay of thermodynamic variables and kinetic constraints, resulting in a rich variety of material-specific phenomena. In this review article, we discuss recent results and insights on transition metal oxidation and rare-earth oxide growth acquired by low-energy electron microscopy and related techniques. We demonstrate that the use of in situ surface sensitive methods is a prerequisite to gaining a deeper understanding of the underlying concepts and the mechanisms responsible for the emerging oxide structure and morphology. Furthermore, examples will be provided on how structural and chemical modifications of the oxide films and nanostructures can be followed in real-time and analyzed in terms of local reactivity and cooperative effects relevant for heterogeneous model catalysis.